Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $v$ a solution of he heat equation, given by $\frac{\partial v}{\partial t}(t,x)=\frac{\partial^2v}{\partial x^2}(t,x)$ for $t>0,x\in\mathbb R$ with the following properties

$v(0,x)=u_0(0) \forall x\in[0,1]$



Now I evolve the periodic function $v$ in a fourier series $v(t,x)=\sum_{k=-\infty}^{\infty}a_k(t)e^{\pi ikx}$

Question: Why does $a_k$ has to satify the differential equations $a_k'(t)=-\pi^2k^2a_k(t)$ ?

share|cite|improve this question
up vote 3 down vote accepted

Let $v(t,x)=\sum\limits_{k=1}^\infty a(k,t)\sin k\pi x+\sum\limits_{k=0}^\infty b(k,t)\cos k\pi x$ so that it automatically satisfies $v(t,x+2)=v(t,x)$ ,

Then $\sum\limits_{k=1}^\infty a_t(k,t)\sin k\pi x+\sum\limits_{k=0}^\infty b_t(k,t)\cos k\pi x=-\sum\limits_{k=1}^\infty k^2\pi^2a(k,t)\sin k\pi x-\sum\limits_{k=0}^\infty k^2\pi^2b(k,t)\cos k\pi x$

$\therefore a_t(k,t)=-k^2\pi^2a(k,t)$ and $b_t(k,t)=-k^2\pi^2b(k,t)$

$a(k,t)=A(k)e^{-k^2\pi^2t}$ and $b(k,t)=B(k)e^{-k^2\pi^2t}$

$\therefore v(t,x)=\sum\limits_{k=1}^\infty A(k)e^{-k^2\pi^2t}\sin k\pi x+\sum\limits_{k=0}^\infty B(k)e^{-k^2\pi^2t}\cos k\pi x$


$\sum\limits_{k=1}^\infty A(k)e^{-k^2\pi^2t}\sin k\pi x+\sum\limits_{k=0}^\infty B(k)e^{-k^2\pi^2t}\cos k\pi x=-\sum\limits_{k=1}^\infty A(k)e^{-k^2\pi^2t}\sin(k\pi(-x))-\sum\limits_{k=0}^\infty B(k)e^{-k^2\pi^2t}\cos(k\pi(-x))$

$\sum\limits_{k=1}^\infty A(k)e^{-k^2\pi^2t}\sin k\pi x+\sum\limits_{k=0}^\infty B(k)e^{-k^2\pi^2t}\cos k\pi x=\sum\limits_{k=1}^\infty A(k)e^{-k^2\pi^2t}\sin k\pi x-\sum\limits_{k=0}^\infty B(k)e^{-k^2\pi^2t}\cos k\pi x$

$\sum\limits_{k=0}^\infty2B(k)e^{-k^2\pi^2t}\cos k\pi x=0$


$\therefore v(t,x)=\sum\limits_{k=1}^\infty A(k)e^{-k^2\pi^2t}\sin k\pi x$

$v(0,x)=u_0(x)~\forall x\in[0,1]$ :

$\sum\limits_{k=1}^\infty A(k)\sin k\pi x=u_0(x)~\forall x\in[0,1]$

$A(k)=2\int_0^1u_0(x)\sin k\pi x~dx~\forall x\in[0,1]$

$\therefore v(t,x)=\sum\limits_{k=1}^\infty2\int_0^1u_0(x)\sin k\pi x~dx~e^{-k^2\pi^2t}\sin k\pi x~\forall x\in[0,1]$

share|cite|improve this answer
It took me some time to get through, but that seems legit :) – bonext Dec 7 '12 at 20:11

Quick hint: substitute your series for $v(t,x)$ to heat equation.

share|cite|improve this answer
Thanks, I have one more question concerning the fourier coefficients $a_k(t)$. Why are they given by $a_k(t)=\frac{1}{2}\int_{-1}^{1}v(0,y)e^{-\pi iky}dy=\frac{1}{i}\int_{0}^{1}sin(\pi ky)dy$ – Montaigne Dec 7 '12 at 16:16
You got something wrong in the above formula and also in your question. Your initial condition should be $v(0,x)=u_0(x)$, and here I assume you wanted to write $a_k(0)$? If that's the case, then here's why you do that: your fourier series for $v(t,x)$ led to a number of ODEs to find $a_k(t)$, so in order to solve these ODEs you have to find initial values ($a_k(0)$). This is done by simply expanding your initial condition $v(0,x)$ into fourier series and taking coefs. for same k's. Does it help? – bonext Dec 7 '12 at 16:30
Yes I want to calculate $a_k(0)$. I know that $v(t,x)=\sum_{-\infty}^{\infty}a_k(0)e^{-\pi^2 k^2 t}e^{\pi ikx}$. Now I set t=0. $v(0,x)=u_0(x)=\sum_{-\infty}^{\infty}a_k(0)e^{\pi ikx}$, but how to derive $a_k(0)$ now? – Montaigne Dec 7 '12 at 16:50
Like any other fourier coef, by integration: $a_k(0)=\int_0^1 u_0(x) e^{i\pi k x}dx$ – bonext Dec 7 '12 at 20:23

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.